Perlindungan Anak Sebagai Korban Eksploitasi Seksual - Bherta, Rika (Universitas Proklamasi 45, 2021)
Children are not adults in miniature, they need the support, and protection from adults, families, communities, governments, and countries. More and more girls are victims of child exploitation and their rights as children have been taken away. The research method was carried out by library research using primary legal materials and secondary legal materials. The research method used was doctrinal legal research or literature research with qualitative methods presented descriptively.The results of this study indicate that repressive legal protection is to apply Article 66 of Law Number 35 of 2014 concerning Child Protection through the dissemination and/or socialization of the provisions of laws and regulations relating to the protection of economically and/or sexually exploited children, monitoring, reporting, and imposing sanctions; and the involvement of various companies, trade unions, non-governmental organizations, and the community in the elimination of economic and/or sexual exploitation of children. While preventive protection is the State, Government, Regional Government, Community, Family, and Parents or Guardians are obliged and fully responsible for the implementation of Child Protection.